SEROLOGICAL SURVEY OF LYME BORRELIOSIS IN THE SOUTH REGION OF KAZAKHSTAN - Kuligin, A.; Lushova, A.; Kan, S.; Bissenbay, A.; Perfilyeva, Yu.; Abdolla, N.; Dmitrovskiy, A.; Skiba, Yu.; Ospanbekova, N.; Davlyatshin, T.; Abuova, G.; Bayakhmetova, M.; et al. (Eurasian Journal of Applied Biotechnology, 2024)
Lyme borreliosis (LB) is an infectious disease caused by spirochetes of the Borrelia burgdorferi sensu lato complex. Transmission occurs through the bites of hard ticks within the genus Ixodes. Cases of fever of unknown origin are recorded in southern Kazakhstan, however, the prevalence of LB in this area remains unstudied. Almaty oblast is recognized as an endemic area for LB. Ixodid tick vectors also inhabit Jambyl oblast, where antibodies to LB agent were previously detected among residents, while it is classified as non-endemic. Turkistan oblast is also considered non-endemic for LB. The purpose of this study was to investigate the seroprevalence of IgG antibodies to B. burgdorferi s.l. among apparently healthy residents of Almaty city (Almaty oblast), Taraz city (Jambyl oblast), and Shymkent city (Turkistan oblast). A total of 465 human serum samples were collected from March 2022 to September 2023. Using the ELISA method, we detected the presence of IgG antibodies to the LB agent in 5.4% of the entire study group (24/465, 95% CI: 3.3-7.6%), and specifically in 9.3% of residents of Almaty city (11/118, 95% CI: 4.7-16.1%, p=0.03), 4.5% – Taraz city (11/242, 95% CI: 2.3-8.0%) and 1.9% – Shymkent city (2/105, 95% CI: 0.2-6.7%). The results of the study confirm the seroprevalence of IgG antibodies to B. burgdorferi s.l. among the population of Almaty city and Jambyl oblast, and also reveal seropositive samples in residents of Turkistan oblast, suggesting possible infection during travel to endemic regions. It is important to continue LB surveillance in endemic and emerging regions, as well as to raise awareness of the infection among healthcare workers and the general public in non-endemic areas.